Evaluation of Soil Microbial and Enzymatic Activity in Ecosystems in a Coastal Region of Brazil - Pupin, Breno [UNESP] (2024)
The enormous soil carbon pool stored by mangroves depends upon microbial respiratory activities and enzymes associated with carbon breakdown in soils. Our hypothesis is that increased microbial activity leads to elevated carbon breakdown. To prove this, we measured microbial respiratory and enzyme activity for nitrogen, phosphorus, and carbon cycle in soil from three coastal ecosystems: mangroves, restinga, and Atlantic forest. The multivariate ordination analysis showed that each treatment had distinct soil microbial activity according to the soil layer and seasons. Our results suggest that the Atlantic forest ecosystem had the highest respiration activity (i.e., CO2-C release), dehydrogenase, phosphatase, protease, and urease activities, while mangroves and sandy coastal plains (called restinga) had lower respiration and enzyme activity. Therefore, soil microbial respiratory activity variation was influenced by soil microbial activity in the most superficial layer in coastal soil ecosystems. The agreement between dehydrogenase activity and CO2-C respiration measurements suggests that microbial activity is an efficient indicator of carbon breakdown. Our findings also indicate that the vegetation type in the different ecosystems contribute to stimulate the soil microbiota increasing both its microbial activity and carbon storage. These issues should be considered for the conservation policies to promote effective protection of vital coastal ecosystems in Brazil. Understanding the coastal ecosystem-induced nutrient shifts in microbial communities is important because they can lead to lagged and multiplicative effects on carbon storage. Taken together, our results illustrate the identification of keystone (organic carbon and microbial activity) as an indicator to offer evidence-providing tools to achieve more ecologically efficient managing practices. Graphical Abstract: (Figure presented.).